ANALYSIS OF THE NOVELS ENTROK AND PASUNG JIWA THROUGH THE LENS OF LIBERAL FEMINISM BY OKKY MADASARI - Isma Safitri Patty, Azhwani; Liliani, Else; Efendi, Anwar; Kelibay, Ismed (JURNAL KONFIKS, 2026)
This study conducts a comparative analysis of Okky Madasari’s novels Entrok and Pasung Jiwa through the perspective of Liberal Feminism. Entrok portrays the social reality of rural Javanese communities during the New Order era, where women are trapped within the chains of tradition, poverty, and cultural myths. Meanwhile, Pasung Jiwa presents contemporary urban dynamics through the characters Sasana and Cak Jek, who attempt to challenge the boundaries of identity, sexuality, and individual freedom. This research employs a qualitative, library-based approach. The primary data sources consist of Madasari’s Entrok and Pasung Jiwa, supported by additional materials gathered from scholarly literature, including relevant journal articles and theoretical studies. The analysis is carried out through close reading and theoretical interpretation, focusing on the manifestation of personal rights, individual rationality, and the pursuit of freedom as core values of liberal feminism. The findings reveal that Okky Madasari consistently highlights the tension between oppressive social structures and individual aspirations for self-determination. This study offers a theoretical contribution by shifting the analytical focus from collective resistance to a rearticulation of personal autonomy within contemporary Indonesian literature.